2010
DOI: 10.1111/j.1365-2478.2009.00830.x
|View full text |Cite
|
Sign up to set email alerts
|

Conforming Falcon gravity and the global gravity anomaly

Abstract: A B S T R A C TGravity derived only from airborne gravity gradient measurements with a normal error distribution will have an error that increases with wavelength. It is straightforward in principle to use sparsely sampled regional gravimeter data to provide the long wavelength information, thereby conforming the derived gravity to the regional gravity. Regional surface or airborne gravimeter data are not always available and can be difficult and expensive to collect in many of the areas where an airborne grav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 13 publications
(18 reference statements)
0
21
0
1
Order By: Relevance
“…이를 극복하기 위하여 최근에 는 벡터 중력을 도입하려는 경향이 있지만 (Krahenbuhl et al, 2014), 벡터 중력계는 아직 상용화 단계가 아 니므로 현장에 적용하기 위해서는 많은 시간이 필요 하다 (Rim and Li, 2013). 반면 중력 변화율 텐서의 측정은 여러 개의 가속도계를 복합적으로 이용하는 중력 변화율 측정 시스템이 개발되어 활발히 이용되 고 있다 (Dransfield, 2010;Lee, 2001). 중력 변화율 텐서는 기본적으로 서로 독립인 5개의 성분이 존재 하므로 중력이나 벡터 중력에 비해 정보의 양이 비 약적으로 증가하므로 이를 응용하려는 다양한 연구들 이 수행되고 있다 (Zhdanov et al, 2004;Beike, 2010;Beike and Pedersen, 2010;Rim and Li, 2012;Martinez et al, 2013;Braga et al, 2014).…”
Section: 서 론unclassified
“…이를 극복하기 위하여 최근에 는 벡터 중력을 도입하려는 경향이 있지만 (Krahenbuhl et al, 2014), 벡터 중력계는 아직 상용화 단계가 아 니므로 현장에 적용하기 위해서는 많은 시간이 필요 하다 (Rim and Li, 2013). 반면 중력 변화율 텐서의 측정은 여러 개의 가속도계를 복합적으로 이용하는 중력 변화율 측정 시스템이 개발되어 활발히 이용되 고 있다 (Dransfield, 2010;Lee, 2001). 중력 변화율 텐서는 기본적으로 서로 독립인 5개의 성분이 존재 하므로 중력이나 벡터 중력에 비해 정보의 양이 비 약적으로 증가하므로 이를 응용하려는 다양한 연구들 이 수행되고 있다 (Zhdanov et al, 2004;Beike, 2010;Beike and Pedersen, 2010;Rim and Li, 2012;Martinez et al, 2013;Braga et al, 2014).…”
Section: 서 론unclassified
“…The airborne gravity (GT-1A) survey was flown at a constant barometric altitude of 2100 m and a line spacing of 2 km in north-south direction (Ameglio, 2005;Dransfield, 2010). The AGG survey comprised two blocks covering the western and eastern parts of the Vredefort dome area.…”
Section: Agg Data From the Vredefort Domementioning
confidence: 99%
“…Dransfield (2010) showed that the DNSC08 (global gravity data released by the Danish National Space Center, 2008), ground, airborne gravity (GT-1A) can be used to improve the long wavelength anomalies of the gravity data derived from Falcon AGG data. The conformed vertical component of the gravity vector over the Vredefort dome area gridded with a cell size of 250 m is shown in Figure 5.3.…”
Section: Agg Data From the Vredefort Domementioning
confidence: 99%
“…Although Φ z commonly is not directly measured in GGT survey, it can be calculated by using the measured vertical gravity gradient ( Φ zz ) and regional ground gravity data (Dransfield, 2010). …”
Section: Eigenvector Analysis Of Ggtmentioning
confidence: 99%
“…Pedersen and Rasmussen, 1990;Zhdanov et al, 2004;Fedi, et al, 2005;Dransfield, 2010;Beiki et al, 2011). Various platforms, such as airborne, ground, and satellites have been utilized for GGT data observation.…”
Section: Introductionmentioning
confidence: 99%